The Pengaruh Profitabilitas, Free Cash Flow dan Leverage Terhadap Manajemen Laba dengan Tata Kelola Perusahaan sebagai Variabel Moderasi - Fanny Pricillia; Estralita Trisnawati; Verawati Verawati (Owner : Riset dan Jurnal Akuntansi, 2025)
The COVID-19 pandemic is a challenge for the Indonesian economy, including companies in the cyclical and non-cyclical sectors which are experiencing a decline in production and income which has an impact on share prices and investor confidence. Therefore, to attract the attention of investors, management often tries to maximize profits through earnings management in financial reports. This is done with the aim of enabling the company to increase or decrease profits according to management's needs and desires, so that the company's financial reports look good in the eyes of interested parties. Several factors that can influence earnings management are profitability, free cash flow and leverage. This research aims to obtain empirical evidence regarding the influence of profitability, free cash flow and leverage on earnings management with corporate governance as a moderating variable in cyclical and non-cyclical sector companies listed on the Indonesia Stock Exchange. The population used in this research was 50 cyclical and non-cyclical sector companies listed on the Indonesia Stock Exchange in 2020-2023. The sample size was determined using a purposive sampling technique. This research is a quantitative research that uses Eviews version 13 software to process data. The results of this research indicate that profitability has no effect on earnings management. Free cash flow and leverage have a positive effect on earnings management. Corporate governance as a moderating variable is unable to moderate the influence of profitability on earnings management. Corporate governance as a moderating variable strengthens the influence of free cash flow and leverage on earnings management.